E-Service Dalam Bursa Kerja Pada Dinas Tenaga Kerja Dan Transmigrasi Di Kabupaten Gowa - Andi Muh Fikram AW; Musliha Karim; Adnan Ma'ruf (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
The objectives of this research are to find out the application of electronic service (E-Service) in job fair and to discover the supporting and inhibiting factors which is found in Labor and Transmigration Department of Gowa Regency. The amount of the informant in this research is 8 people. This research applies the qualitative method in phenomenology type which emphasized in the subjectivity of human life experience. Technique of data collection used observation method, interview, and documentation. The result of the research showed that E-service in job market has not been reached maximally which could be seen from the aspectof service provider hereby the officers who ran the dutieshave not fully succeeded in bringing satisfactory service to the community even though it has corresponded with procedural work. From others aspects such as service users and line service have not been achieved also. Supporting factor was the attitude of leadership and the interest of the use and utilization of information technology while the insisting factor was infrastructure and human resources.